2019
DOI: 10.1111/vox.12786
|View full text |Cite
|
Sign up to set email alerts
|

Biologic roles of the ABH and Lewis histo‐blood group antigens part II: thrombosis, cardiovascular disease and metabolism

Abstract: The ABH and Lewis antigens were among the first of the human red blood cell polymorphisms to be identified and, in the case of the former, play a dominant role in transfusion and transplantation. But these two therapies are largely twentieth‐century innovations, and the ABH and related carbohydrate antigens are not only expressed on a very wide range of human tissues, but were present in primates long before modern humans evolved. Although we have learned a great deal about the biochemistry and genetics of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 177 publications
(232 reference statements)
0
56
0
1
Order By: Relevance
“…Recently, Groot et al reported that people with A, B, and AB blood types are more susceptible to thrombosis and myocardial infarction, while those bearing the O blood group are more prone to hypertension [11]. In addition, individuals having the A antigen are also predisposed to a higher risk of metabolic disorders, such as hyperlipidemia and diabetes mellitus [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Groot et al reported that people with A, B, and AB blood types are more susceptible to thrombosis and myocardial infarction, while those bearing the O blood group are more prone to hypertension [11]. In addition, individuals having the A antigen are also predisposed to a higher risk of metabolic disorders, such as hyperlipidemia and diabetes mellitus [12].…”
Section: Introductionmentioning
confidence: 99%
“…These authors also reported that people with A, B and AB blood types are more likely to develop thrombosis and myocardial infarction, while those with type O are more likely to develop hypertensive conditions. The A antigen also seems to predispose individuals to a greater risk of thromboembolism and metabolic disorders, such as hyperlipidemia, hypercholesterolemia and diabetes mellitus [66] .…”
Section: Supporting Evidence Of the Hypothesismentioning
confidence: 99%
“…For cardiovascular effects, it is suggested that individuals carrying the A antigen have a higher prevalence of thromboembolism due its association with high levels of von Willebrand factor [67] , a glycoprotein synthesized and secreted by endothelial cells and megakaryocytes that stimulates coagulation [68] . In this particular case, it is speculated that antigen A, as well as B, act by increasing the secretion of the factor or by decreasing its clearance, or both [66] .…”
Section: Supporting Evidence Of the Hypothesismentioning
confidence: 99%
“…In addition to their role in host-pathogen interactions, which are largely mediated by ABH glycan expression on epithelial cells, ABH antigens are also expressed on endothelial cells and platelets, where they influence endothelial activation and coagulation [9]. The importance of the ABH antigens in these processes is highlighted by the well-established increase in risk of both cardiovascular and thromboembolic disease in patients with non-O blood types [10,11] The established role of many of these proteins in inflammatory vascular leak led to the hypothesis that ABO genotype may alter ARDS risk and contribute to heterogeneity of pulmonary responses to inflammatory stimuli.…”
Section: Diverse Roles For Abh Glycosylationmentioning
confidence: 99%